Extracellular Vesicles as Mediators and Potential Targets in Combating Cancer Drug Resistance - Zhang, Haodong; Wu, Bohan; Wang, Yanheng; Du, Huamao; Fang, Liaoqiong (Molecules (Basel, Switzerland), 2025)
Extracellular vesicles (EVs) are key mediators in the communication between cancer cells and their microenvironment, significantly influencing drug resistance. This review provides a comprehensive analysis of the roles of EVs in promoting drug resistance through mechanisms such as drug efflux, apoptosis resistance, autophagy imbalance, and tumor microenvironment modulation. Despite extensive research, details of EVs biogenesis, cargo selection, and specific pathways in EVs-mediated drug resistance are not fully understood. This review critically examines recent advancements, highlighting key studies that elucidate the molecular mechanisms of EVs functions. Additionally, innovative therapeutic strategies targeting EVs are explored, including inhibiting EVs biogenesis, engineering EVs for drug delivery, and identifying resistance-inhibiting molecules within EVs. By integrating insights from primary research and proposing new directions for future studies, this review aims to advance the understanding of EVs in cancer biology and foster effective interventions to mitigate drug resistance in cancer therapy.